2022
DOI: 10.3390/antibiotics11091231
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baylyi Strain BD413 Can Acquire an Antibiotic Resistance Gene by Natural Transformation on Lettuce Phylloplane and Enter the Endosphere

Abstract: Antibiotic resistance spread must be considered in a holistic framework which comprises the agri-food ecosystems, where plants can be considered a bridge connecting water and soil habitats with the human microbiome. However, the study of horizontal gene transfer events within the plant microbiome is still overlooked. Here, the environmental strain Acinetobacter baylyi BD413 was used to study the acquisition of extracellular DNA (exDNA) carrying an antibiotic resistance gene (ARG) on lettuce phylloplane, perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Here, we show evidence indicating that A. baumannii has ligninolytic activity by depolymerization through two lignin peroxidases (DyP1A and DyP1B; ACX60_09835 and ACX60_RS17375 respectively, Figure S1), consistent with gene products we found in a bioinformatics search for each step necessary to fully degrade Lignin and to feed its products into the TCA cycle (Figures S1 and S2a–d). We hypothesize that these genes, including the vanABKP operon, are possibly conserved in the species because of a possible original association of the bacterium with plants, considering that A. baylyi is also associated with them (Riva, Mapelli, et al., 2022; Riva, Patania, et al., 2022; Scaccia et al., 2021). Upon seeing the genomic similarity of the VA catabolic pathway between A. baylyi and A. baumannii , we surmised that A. baumannii can use VA as a sole carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we show evidence indicating that A. baumannii has ligninolytic activity by depolymerization through two lignin peroxidases (DyP1A and DyP1B; ACX60_09835 and ACX60_RS17375 respectively, Figure S1), consistent with gene products we found in a bioinformatics search for each step necessary to fully degrade Lignin and to feed its products into the TCA cycle (Figures S1 and S2a–d). We hypothesize that these genes, including the vanABKP operon, are possibly conserved in the species because of a possible original association of the bacterium with plants, considering that A. baylyi is also associated with them (Riva, Mapelli, et al., 2022; Riva, Patania, et al., 2022; Scaccia et al., 2021). Upon seeing the genomic similarity of the VA catabolic pathway between A. baylyi and A. baumannii , we surmised that A. baumannii can use VA as a sole carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…However, both transformation and transduction may easily rival conjugation as a means for AR gene spread. With the millions of copies per milliliter of extracellular DNA encoding carbapenemases being dumped into wastewater [ 213 ]; the fact that fragmented (≥20 bp) and damaged DNA can be acquired by transformation [ 214 ]; that transformation can occur in unexpected places, such as the phylloplane of edible vegetables [ 215 ]; and AR genes being routinely found in phages (even towards the “last resort” antibiotic colistin [ 216 ])—from the fecal “phageome” of healthy humans [ 217 ], food samples [ 218 ] (up to the point that the liver of farm chickens can be considered as a reservoir of AR genes [ 219 ]). Furthermore, genomic islands shared by distantly related bacteria were likely mobilized between them by phages [ 220 ].…”
Section: Non-canonical Horizontal Gene Transfermentioning
confidence: 99%
“…Over the last several decades, conjugative plasmid-mediated horizontal gene transfer (HGT) occurring between bacteria in the environment has acquired a high relevance in public health and environmental sciences [1][2][3][4]. Conjugative plasmids are mobile genetic elements (MGEs), self-replicative and auto-transferable, that usually carry genes involved in antimicrobial resistance, virulence, heavy-metal resistance, and degradation of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies revealed plasmid transfer in compartments of model and agronomically relevant plant species [3,10,14], the presence, diversity, transfer rates, and prevalence of conjugative plasmids in the plant-soil continuum of urban areas or built environments remain an unexplored "black box" [17,22]. In this context, ornamental plants can acquire a special relevance because they are widely planted and grown in many outdoor (e.g., parks, gardens, squares, etc.)…”
Section: Introductionmentioning
confidence: 99%